Reservoirs in a changing world proceedings of the 12th conference of the BDS held at Trinity College, Dublin, 4-8 September 2002 - Tedd, P. (Thomas Telford, 2002)
Reservoir safety is the key theme of these proceedings, with many papers on the performance and rehabilitation of dams. The evolution of reservoirs in Ireland and the development of safety legislation in the UK are described.